Formation of double shell during implosion of plasma metal puff Z-pinches - Shmelev D. L.; Zhigalin A. S. Aleksandr Sergeevich; Chaykovskiy S. A.; Oreshkin V. I. Vladimir Ivanovich; Russkikh A. G. Aleksandr Gennadievich (2020, 2020)
Title screen